Succession and Assembly Mechanism of Bacterial Communities in Different Grades of Jinhui Baijiu Daqu during Storage - REN Haiwei, LI Yunfan, ALIMIRE·Keremu, MA Donglin, GUO Xiaopeng, ZHANG Bingyun,ZHANG Zhiliang, LI Yantao, WEI Junqiang (Shipin Kexue, 2025)
High-throughput sequencing was used to analyze the differences in bacterial community structure among different grades of Jinhui baijiu daqu and the dynamic changes in physicochemical indices were characterized during storage. Moreover, redundancy analysis was used to study the relationship between bacterial genera and physicochemical indexes, and the neutral community and null models were combined to explore the mechanisms underlying bacterial community assembly during the storage of Jinhui baijiu daqu. The results showed that the moisture content of daqu of all three grades tested presented an increasing trend, while the acidity exhibited a decreasing trend during the storage period, which were in the ranges of 11%–13% and 0.9–1.3 mmol/10 g, respectively, conforming to the standards specified in QB/T 4259-2011 Strong flavour daqu. The content of amino nitrogen (3.4–4.7 g/kg), saccharification power (194.4–251.0 mg/(g·h)), fermentation power (0.35–0.42 g/(0.5 g·72 h)), and esterification power (148.7–391.1 mg/(50 g·7 d)) showed an upward trend as well. Firmicutes (61.35%), Proteobacteria (22.98%), and Actinobacteriota (7.25%) were identified as the dominant phyla, and Bacillus (29.58%) and Leuconostoc (9.51%) as the dominant genus. There was a significant negative correlation between Bacillus and lactic acid bacteria (LAB, P < 0.01), while a positive correlation was found among LAB (P < 0.01). Differential bacteria including Bacillus and Thermoactinomyces were identified among grades, and Saccharopolyspora and Thermoactinomyces were found to be the major differential bacteria among three different storage times (0, 45, and 90 days). Pantoea, Saccharopolyspora, and Staphylococcus were positively correlated with esterification power, fermentation power, and amino nitrogen content. We found differences in the degree of involvement of the bacterial communities in metabolic activities and identified 11 significantly differential metabolic pathways, including carbohydrate metabolism, amino acid metabolism, and nucleotide metabolism. Drift variation dominated the stochastic process of bacterial community assembly. Additionally, esterification power, fermentation power, moisture content, acidity, and amino nitrogen content might be the major factors influencing of bacterial community assembly during daqu storage. This study lays the theoretical foundation for understanding bacterial community succession and assembly in Gansu-style nongxiangxing baijiu daqu during storage.